(3GdGbJUGO GdOhdjs - (3SGei(B, (3Ndjds ((3GdbGgQI(B:s (3OGQ GdfgVI GdYQHjI(B,s, 2005)
(3eaghe GdGbJUGO GdOhdj hSjGSJg GdbOjeI heTcdg GdMOjKI , GdfXQjI GdcdGScjI ddJLGQI GdOhdjI , GdJMdjd GdMOjK dfXQjI GdJLGQI GdOhdjI , GdWdH GdJHGOdj hfXQjI GdJLGQI GdOhdjI , gHGJ YhGed GdGfJGL hfXQjI gcJTQ Chgdjf , fXQjI GdJLGQI GdOhdjI GdMOjKI , GSbGW HYV GdaQhV GdeHSWI aj GdJMdjd GdSGHb dfXQjI GdJLGQI GdOhdjI , HYV GdCKGQ GdeJQJHI Ydi GdJLGQI GdOhdjI , Gdfeh GdGbJUGOj hGdJLGQI GdOhdjI , SjGSI GdJLGQI GdOhdjI , bjhO GdJLGQI GdOhdjI (B:(3GdJYQaI GdLeQcjI , bjhO GdJLGQI GdOhdjI (B:(3ZjQ GdVQGFH GdLeQcjI , GdJcGed GdGbJUGOj GdGJMGOGJ GdLeQcjI hefGWb GdJLGQI GdMQI , JGQjN GdSjGSI GdJLGQjI hJGQjN eMGhdGJ GdJcGed GdGbJUGOj, GdJcGed GdGbfUGOj GdYQHj , GdJLGQI GdOhdjI hGdJfejI GdGbJUGOjI , gjcd ejRGf GdeOahYGJ , CShGb GdUQa GdCLfHj hCSYGQ GdUQa s
(3HjHdjhZQGajG U(B.713s
Keywords: (3GbJUGO Ohdjs; (3SjGSGJ GdJLGQI GdOhdjIs; (3fXQjI GdJLGQI GdOhdjIs